EGCG promotes PRKCA expression to alleviate LPS-induced acute lung injury and inflammatory response - Mian Wang (Nature Portfolio, 2021)
Abstract Acute lung injury (ALI), which could be induced by multiple factors such as lipopolysaccharide (LPS), refer to clinical symptoms of acute respiratory failure, commonly with high morbidity and mortality. Reportedly, active ingredients from green tea have anti-inflammatory and anticancer properties, including epigallocatechin-3-gallate (EGCG). In the present study, protein kinase C alpha (PRKCA) is involved in EGCG protection against LPS-induced inflammation and ALI. EGCG treatment attenuated LPS-stimulated ALI in mice as manifested as improved lung injury scores, decreased total cell amounts, neutrophil amounts and macrophage amounts, inhibited the activity of MPO, decreased wet-to-dry weight ratio of lung tissues, and inhibited release of inflammatory cytokines TNF-α, IL-1β, and IL-6. PRKCA mRNA and protein expression showed to be dramatically decreased by LPS treatment while reversed by EGCG treatment. Within LPS-stimulated ALI mice, PRKCA silencing further aggravated, while PRKCA overexpression attenuated LPS-stimulated inflammation and ALI through MAPK signaling pathway. PRKCA silencing attenuated EGCG protection. Within LPS-induced RAW 264.7 macrophages, EGCG could induce PRKCA expression. Single EGCG treatment or Lv-PRKCA infection attenuated LPS-induced increases in inflammatory factors; PRKCA silencing could reverse the suppressive effects of EGCG upon LPS-stimulated inflammatory factor release. In conclusion, EGCG pretreatment inhibits LPS-induced ALI in mice. The protective mechanism might be associated with the inhibitory effects of PRKCA on proinflammatory cytokine release via macrophages and MAPK signaling pathway.